2006
DOI: 10.1111/j.1365-2230.2005.02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis with cutaneous polyarteritis nodosa

Abstract: Cutaneous polyarteritis nodosa presents with typical cutaneous lesions of polyarteritis nodosa without visceral involvement at the time of diagnosis. We report a 32-year-old woman with a 12-year history of myasthenia gravis under immunosuppressive treatment, who presented with tender, erythematous nodules 20 mm in diameter on her shins. A diagnosis of cutaneous polyarteritis nodosa was made, based on the clinical and histopathological findings. Myasthenia gravis, an antibody-mediated disease, is occasionally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…None had aimed to investigate the MG autoantibodies. They had mainly described clinical observations like a paraneoplastic MG with central nervous system lymphoma (12), an association of MG with polyarteritis nodosa (13), and a thymoma accompanied by MG, PRCA, and Good's syndrome (14). Other discussed management of MG like the radiotherapy for thymoma resection (15), the safety of cardiopulmonary bypass 123 and gender, MGFA Class, MG category, thymus status, history of respiratory crisis, choice of treatment, and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None had aimed to investigate the MG autoantibodies. They had mainly described clinical observations like a paraneoplastic MG with central nervous system lymphoma (12), an association of MG with polyarteritis nodosa (13), and a thymoma accompanied by MG, PRCA, and Good's syndrome (14). Other discussed management of MG like the radiotherapy for thymoma resection (15), the safety of cardiopulmonary bypass 123 and gender, MGFA Class, MG category, thymus status, history of respiratory crisis, choice of treatment, and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lebanese studies about MG were very rare and limited to few case reports. These works had only presented some clinical observations and operational methods to manage MG without investigating Correspondence autoantibodies (12)(13)(14)(15). Therefore, the present study aimed at determining the prevalence of different autoantibodies and their association with clinical phenotypes and quality of life (QOL) in a Lebanese group with MG.…”
Section: Introductionmentioning
confidence: 99%
“…While some cases of MG have been associated with vascular pathology, to the best of our knowledge no cases of spontaneous iliopsoas hematoma associated with myasthenic crisis have been reported in the literature [6]. MG has an incidence of 0.21 -2 per 100,000, and while bulbar symptoms including dysphagia, slurred speech, and weakness are the hallmark of the disease, associations with coagulopathy or major bleeding is not well documented [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recently published study by Liozon et al [10], only one case of MG is reported in a series of 250 patients with GCA during a study period of 27 years. We also found one case report describing the concurrence of MG with polyarteritis nodosa [11], as well as a case of myasthenia gravis in the setting of microscopic polyangiitis [12]. …”
Section: Discussionmentioning
confidence: 99%